2017
DOI: 10.18632/oncotarget.18090
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucose metabolism related gene GLUT1 in the occurrence and prognosis of colorectal cancer

Abstract: Colorectal cancer (CRC) ranks the third most commonly diagnosed cancer in males and the second in females worldwide. However, the functional and causal SNPs for CRC remain to be mined. Glucose transporter 1 (GLUT1), a pivotal rate-limiting element in the transport of glucose in malignancy cells, has been identified to be associated with many cancers. Here, we aim to explore the role of GLUT1 in the occurrence and prognosis of colorectal cancer in a Chinese population. We found that GLUT1 expression levels in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 40 publications
1
49
0
1
Order By: Relevance
“…56 GLUT is a family of glucose transporters, and has been extensively studied in cancer cells. As a glucose family, GLUT1 is the predominant transporter usually overexpressed in tumors, including hepatic, 57 lung, 58 colorectal, 59 and breast cancer. 60 The reduction of the expression levels of HIF1α and GLUT1 by EGCG, may represent a mechanism to explain the decrease in glucose consumption following EGCG treatment.…”
Section: Food and Function Papermentioning
confidence: 99%
“…56 GLUT is a family of glucose transporters, and has been extensively studied in cancer cells. As a glucose family, GLUT1 is the predominant transporter usually overexpressed in tumors, including hepatic, 57 lung, 58 colorectal, 59 and breast cancer. 60 The reduction of the expression levels of HIF1α and GLUT1 by EGCG, may represent a mechanism to explain the decrease in glucose consumption following EGCG treatment.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Colorectal cancer (CRC), one of the common malignancies in the human digestive system, ranks third in males and second in females worldwide (Feng et al, 2017). Surveillance and Health Services Research from the American Cancer Society estimates that 147,950 new CRC patients including of 78,300 males and 69,650 females will be diagnosed, and 28,630 men and 24,570 women will die of CRC in 2020 (Siegel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These SNPs have been studied in breast cancer cells through the measurement of fluorescently tagged glucose molecules 18F-FDG; however, there was no association between glucose uptake and these genotypes ( 45 ). However, the rs710218 SLC2A1-AS1 SNP has recently been shown to be associated with increased Glut1 expression in colorectal cancer tissue when at least one copy of the T allele was present in comparison to those with homozygous AA genotypes among individuals with colorectal cancer ( 71 ). These results do not correspond with our own, as we found non-favorable progression among the HIV-positive treatment-naive and elevated CD4+Glut1+ T cell percentage in HIV+/cART individuals to be associated with the rs710218 dominant A allele ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the rs710218 SLC2A1-AS1 SNP has recently been shown to be associated with increased Glut1 expression in colorectal cancer tissue when at least one copy of the T allele was present in comparison to those with homozygous AA genotypes among individuals with colorectal cancer ( 71 ). These results do not correspond with our own, as we found non-favorable progression among the HIV-positive treatment-naive and elevated CD4+Glut1+ T cell percentage in HIV+/cART individuals to be associated with the rs710218 dominant A allele ( 71 ). Furthermore, other studies have shown that this SNP does not influence 18F-FDG uptake in breast cancer ( 72 ), suggesting that regulation of Glut1 expression by SNPs may be cell and context specific.…”
Section: Discussionmentioning
confidence: 99%